Factors associated with cervical cancer screening participation among migrant women in Europe: a scoping review - Marques, Patrícia (2020)
Cervical cancer screening has been effective in reducing incidence and mortality of cervical cancer, leading European countries to implement screening programs. However, migrant women show lower screening participation compared to nationals. This scoping review aims to provide a synthesis of the growing evidence on factors associated with participation in cervical cancer screening among migrant women in Europe.